Hubungan Antara Gratitude dengan Psychological Well-Being pada Mahasiswa Pekerja di Universitas Muhammadiyah Sidoarjo - Rahayu Anjas Sari; Effy Wardati Maryam (Bandung Conference Series: Psychology Science, 2022)
Abstract. This study aims to determine the relationship between Gratitude and Psychological Well-being in working students at the University of Muhammadiyah Sidoarjo. This type of research is a correlational quantitative research with Gratitude as the independent variable and Psychological Well-being as the dependent variable. The number of samples in this study were 368 working students who were determined using the Proportionate Stratified Random Sampling technique. Data retrieval using the Gratitude scale with a reliability value of 0.901, and the Psychological Wella-being scale with a reliability value of 0.918. Based on the results of data analysis using Product Moment Correlation, it shows the correlation coefficient (rxy) of 0.666 with a significance value of 0.000 <0.05, meaning that there is a positive relationship between Gratitude and Psychological Well-being in student workers, where the higher the Gratitude, the higher Psychological Well-being, and vice versa, the lower the Gratitude, the lower the Psychological Well-being of working students at the University of Muhammadiyah Sidoarjo. The Gratitude variable in this study contributed 44.4% to the Psychological Well-being variable. Abstrak. Penelitian ini bertujuan untuk mengetahui hubungan antara Gratitude dengan Psychological Well-being pada mahasiswa pekerja di Universitas Muhammadiyah Sidoarjo. Tipe penelitian ini merupakan penelitian kuantitatif korelasional dengan Gratitude sebagai variabel independen dan Psychological Well-being sebagai variabel dependen. Jumlah sampel pada penelitian ini sebanyak 368 mahasiswa pekerja yang ditentukan menggunakan teknik Proportionate Stratified Random Sampling. Pengambilan data menggunakan skala Gratitude dengan nilai reliabilitas sebesar 0,901, dan skala Psychological Well-being dengan nilai reliabilitas sebesar 0,918. Berdasarkan hasil analisa data dengan menggunakan Korelasi Product Moment menunjukkan nilai koefisien korelasi (rxy) sebesar 0,666 dengan nilai signifikansi 0,000 < 0,05, artinya terdapat hubungan positif antara Gratitude dengan Psychological Well-being pada mahasiswa pekerja, dimana semakin tinggi Gratitude maka semakin tinggi Psychological Well-being, dan sebaliknya, semakin rendah Gratitude maka semakin rendah Psychological Well-being pada mahasiswa pekerja di Universitas Muhammadiyah Sidoarjo. Variabel Gratitude pada penelitian ini memberikan sumbangan sebesar 44,4% terhadap variabel Psychological Well-being.